Correction to: Factors associated with poor treatment outcome of tuberculosis in Debre Tabor, northwest Ethiopia - Addisu Melese; Balew Zeleke (BMC Research Notes, 2020)
Following publication of the original article [1], similarity with another article by the same authors was reported. The authors would like to clarify that the current study [1] is an update of previous work that used the same data set in the analysis [2]. In Melese and Zeleke [1], the authors found that factors associated with poor treatment outcome were not sufficiently addressed previously. As a result of the reanalysis the effective sample size has changed.